Factors influencing farmers' decisions to continue rice farming in Pemunduran Village, Kumpeh Ulu Subdistrict, Muaro Jambi Regency - Sardi, Idris; zakiah, Zakiah; Affandy, Ferdy (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2026)
This study aims to: 1) Identify factors related to rice farmers' decisions to continue farming in Pemunduran Village, Kumpeh Ulu Subdistrict; 2) Identify farmers' decisions to continue rice farming in Pemunduran Village. The sampling method used in this study was census sampling. The data analysis methods used were descriptive analysis and Chi-Square with a 2x2 contingency table. The results of the study can be concluded that the decision of farmers in Pemunduran Village to continue rice farming is influenced by six main factors: personal consumption, farmer experience, social environmental factors, habitual factors, government policy, and land. Most farmers in Pemunduran Village allocate more than half of their land to rice cultivation, indicating that their level of decision to continue rice cultivation is relatively high. This can be seen where the majority of farmers allocate more than 50% of their land to rice farming, with the highest percentage category being personal consumption